Algumas aplicações da trigonometria - Silva, Victor Wender Soares (Universidade Federal do Tocantins, 2020)
About 2300 years ago, a man created a method to calculate the distance from the Earth to the Sun and from the Earth to the Moon. At the same era, another man was able to calculate the circumference of the Earth with great precision, using only primitive instruments and the brain. How did they manage to make such discoveries? Despite being devoid of technical resources and technology of the modern world, these men had as an ally the part of mathematics that studies the relations between the sides and angles of a triangle, and that makes possible the calculation of these enormous distances and measures: the Trigonometry. The aim of this monograph is to highlight the importance of theoretical studies, theoretical applications and practical applications of Trigonometry in some sciences and areas of human knowledge, and the relevance that these studies and applications have in people’s lives. In the course of the work, we will study Trigonometry and its properties, in order to analyze the context of its applications in some sciences and/or areas of human knowledge. We will also conduct a practical experiment in order to demonstrate one of these applications.